Implementation of Character Education in Elementary Schools (Comparative Study between SDIT and Public Elementary Schools in West Lombok) - Juniarti, Insani; Ramadhanti, Fitrah; Murdani, Murdani; Asmawati, Windi; Lestari, Ita; Setiadi, Dadi; Sumardi, Lalu (International Journal of Education and Digital Learning (IJEDL), 2024)
This study aims to analyze the implementation of character education in Integrated Islamic Elementary Schools (SDIT) and Public Elementary Schools (SDN) through a comparative approach. Character education plays a crucial role in shaping students' personalities, fostering responsibility, and promoting integrity. The research adopts a case study methodology to explore how character education is implemented in two distinct school environments. Data was gathered through observations, interviews, and documentation at SDIT and SDN schools in West Lombok. The findings indicate that SDIT offers a more structured, religiously oriented, and integrated character education program within the curriculum. This includes practices such as morning dhikr, prayer guidance, and the use of habit tracking books at home. SDIT also conducts formal evaluations using quantitative data, such as recording violations and assessing students' affective values. These evaluations are discussed during monthly meetings and annual work reviews. In contrast, SDN focuses on a simpler, habit-based approach, emphasizing activities like prayer before class, class duties, and extracurricular activities. However, there are no formal tools in place for evaluation. As a result, SDIT tends to be more attractive to parents compared to Public Elementary Schools.